Educational Board Games: “Gues Who?” As An Optimization Of Children's Learning Focus In Learning PPKn In Elementary School - Zakiyyah Afrahas Sholikhah; Rosilah Minarsyil; Lina Ariani; Deni Zein Tarsidi (Academic Solution Publisher, 2024)
The background of this research is the importance of effective learning strategies to increase learners' focus and involvement in learning Civic Education (PPKn) in elementary schools. This study aims to examine the effectiveness of educational games based on board games, namely “Guess Who?”, in optimizing students' attention and participation during learning. The research method used is a qualitative approach with a case study method, and data collection techniques with interviews, observations, and literature studies. The results showed that the use of the “Guess Who?” board game can increase students' concentration, active participation, and understanding of Civics material. In conclusion, “Guess Who?” is an effective and interactive learning media, which can help optimize students' learning focus in learning Civics in elementary schools.